L'autruche. Elevage et rentabilité - Lebailly, Philippe (Uliège Library, 1998)
This book is the continuation of a study carried out for the Ministry of the Walloon Region and the European Union, which aimed to analyze the profitability of an ostrich farm in Belgium. Fresh ostrich meat has been an integral part of the supermarket shelves for some years now. The demand for ostrich meat is growing rapidly. This meat combines gastronomy and dietetics thanks to its low fat content, high protein content and high tenderness. The European market is mainly supplied from South Africa. However, since the nineties, a real geographical diversification of the production has been observed and the species acclimates very well in countries with a temperate climate. Belgium currently has between 120 and 150 farms, for an estimated herd of 5000 animals. In addition to the very promising valorization of the meat, one will also note that of the leather and, to a lesser extent, that of the feathers. This book is intended for a wide audience: breeders, researchers, decision-makers and financial actors. In particular, it aims at enlightening the candidate breeder willing to invest in ostrich breeding, which implies a good knowledge of the requirements and the technicality of such a speculation. It is also necessary to be aware of the fact that the ostrich market evolves rapidly and should also experience periods of less favorable conditions. In this case, the economic analyses carried out in this book show, taking the example of a farm for fattening, that a reasoned evaluation of profitability is a prerequisite for an investment decision.